2012
DOI: 10.1063/1.3693618
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and compensation of the nonlinear response in photomultiplier tubes for quantitative single-shot measurements

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Severe signal distortions can occur to the measured signal if the detector is operating in its nonlinear region. The importance of detector linearity in phosphor thermometry was characterized and reported by Knappe et al [25,26]. The studies showed that photodetectors can severely distort the shape of the exponentially decaying signals.…”
Section: Detector Linearitymentioning
confidence: 99%
“…Severe signal distortions can occur to the measured signal if the detector is operating in its nonlinear region. The importance of detector linearity in phosphor thermometry was characterized and reported by Knappe et al [25,26]. The studies showed that photodetectors can severely distort the shape of the exponentially decaying signals.…”
Section: Detector Linearitymentioning
confidence: 99%
“…A well-constructed calibration curve is important for an accurate thermographic phosphor temperature determination. The process of obtaining a phosphor calibration curve can be tedious and accompanied with effects such as detector nonlinearity [13,14]. Despite the importance of the calibration, no major development has occurred or been reported for the method by which the temperature calibration is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Being semi-invasive as it requires to add a thin coating of phosphor particles, this techniqueoften named laser-induced phosphorescence (LIP)-uses rare-earth-doped ceramic phosphors whose spectroscopic properties are highly sensitive to temperature (Allison and Gillies 1997;Khalid and Kontis 2008;Chambers and Clarke 2009). In practice, this technique can be either implemented in the temporal domain, by measuring the phosphorescence glowing after excitation (Knappe et al 2012), or in the spectral domain, by estimating a ratio of intensities (Feist et al 2002). Fuhrmann et al (2013) performed a systematic study of these two approaches and showed the advantages of the lifetime method, which is used in this study.…”
Section: Introductionmentioning
confidence: 99%